Emisi Karbon Lahan Gambut pada Agroekosistem Kelapa Sawit - M. B. Prayitno; Sabaruddin Sabaruddin; D. Setyawan; Yakup Yakup (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Carbon emissions is one of the activities of agroecosystem impacts of oil palm on peat land as a result of the making drainage and plant growth. This research was conducted in the area of oil palm agroecosystem on peat land landscape, Ogan Komering Ilir District, South Sumatra with the aim of estimating reserves and carbon emissions on the land. Contribution of carbon emissions on the land with plant age 5, 3 and 2 years without drainage channels are respectively 12.027; 11.262 and 9.783 tons CO2/year, as well as plants age of 5 years with the drainage channel is 14.723 tons of CO2/year. Contribution of carbon emissions from the making drainage channel reaches 2,696 tons of CO2/ha/year and greater than the contribution of carbon emissions from the aging plant palm oil annually, amounting to 0.383 to 1.479 tons of CO2/ha/year.